Experimental study on the effects of different disinfectants in preventing pin-site infection after using Ilizarov circular external fixators. (October 2020) - Guo, Xiujuan; Zhang, Yonghong; Li, Pengcui; Guo, Jinli
The present study aimed to investigate the effects of different disinfectants in preventing pin-site infection. A total of 32 healthy New Zealand white rabbits were selected as the research subjects. The rabbits were placed in an Ilizarov 3/4 circular external fixator for a period of time after feeding. They were then divided into four groups of eight animals each. After surgery, pin-site nursing was performed twice a day with a different disinfectant for each group (chlorhexidine gluconate alcohol disinfectant, Maokang iodine, 75% alcohol and physiological saline). Each pin site's surrounding conditions were visually observed daily, and bacterial culture of the pin-site secretions was promptly performed. The changes of C-reactive protein (CRP) and white blood cell upon the first day, first week, second week, fourth week, and sixth week after the operation were compared, as were infection statuses and morphological changes in the surrounding tissue at the sixth week post operation. The differences in the CRP and white blood cell values and infection rates among the four groups were found to be statistically significant (P < 0.05), but the difference in infection levels among the four groups was not statistically significant (P>0.05). In addition, the difference in the pathologically inflammatory cells among the four groups at the sixth week post operation was statistically significant (P < 0.05).It was concluded that the effect of chlorhexidine gluconate alcohol disinfectant in preventing pin-site infection was superior compared to the other three disinfectants .